Faktor Kesejahteraan Objektif dalam Subjektifitas Penerima Manfaat Program Keluarga Harapan di Wilayah Perkotaan - Topik Ismail; Septiana Dwiputranti; Nita Nurliawati (Jurnal Media Administrasi Terapan, 2023)
Subjective welfare is obtained from various internal and external factors in improving family welfare. Therefore, this study aims to look at the prevalence of the factors that shape the question of the welfare of the beneficiaries from the basic components/conditions of needs and welfare. A cross-section is used in this study because it is carried out in a certain period in view of the objective experience of subjective well-being. Therefore, we performed univariate and bivariate analyzes with chi-square tests to check for cross-relationships between variables. Research shows that one of the three basic needs is less relevant in shaping the quality of life, namely education. Meanwhile, welfare conditions (natural, economic, political, social, infrastructure, public services) in urban areas have a relationship in shaping the subjective well- being of beneficiaries, even though they are in critical or good conditions. There is a significant relationship between health, living standards, and all spheres of welfare in urban areas that shape the subjective well-being of beneficiaries and beneficiaries with their demographic characteristics showing that they are still below the poverty line. Therefore, the recommendation is addressed to the regional/central government to pay more attention to the quality of life of poor households in viewing and welfare through increasing human resources through efforts to improve the social economy to meet basic needs and improve the quality and accessibility of services. Because the quality of life is part of the goal of human development.